Impact of digital maturity to employee's productivity and performance: basis for human resource management operation transformation program - Manoy, Mark Andrew M. (Parañaque City: Olivarez College, 2022)
The study intended to analyze the productivity and performance of employees in business technology companies by assessing their maturity level and its progression through digital transformation. The output of the study aims to provide the management the perspective, ability to evaluate, measure and improve productivity and performance through relevant and systemized information for decision making. To capture data, produce information and achieve its purposes, the researcher utilized the quantitative descriptive correlational method through a self-assessment survey disseminated to 325 employees across three business technology companies in Makati City. Results showed that majority of the respondents are classified as younger generation. The business technology industry employs younger workforce mainly on consideration of productivity, competitiveness, and the fact that many young talented workers are considered highly technology-led and are constantly chasing the most up to date technology. Consequently, relationship of maturity level on employees' productivity and performance are significantly related. Through this, three proposed programs are provided to business technology companies to strategically place the business to substitute optimal and improved business activities with respect to maturity level and employees productivity and performance. This study contributes to the business improvements of business technology companies through the implementation of Human Resource Management Operation Transformation Program as part of business continuous improvements.
Master Thesis
Keywords: Business Technology; Human Resources; Maturity level; Digital transformation